The Role of Woman in Ghasemabadi Dance with an Emphasis on the Ritual of Rice Farming - Seyedeh Farkhondeh Pournasran; Narges Zaker Jafari (زن در فرهنگ و هنر, 2024)
The majority of the labor force engaged in rice cultivation within the province of Guilan consists of rural women who possess extensive practical expertise in their respective fields; thus, their presence assumes particular significance. Women show the rituals of rice farming, i.e. planting, planting and harvesting, in performing rituals such as the Ghasemababdi dance, which, in addition to visual appeal, express a spiritual and mythological bond with nature. The purpose of this study is to provide an answer to the question of the significance of women's presence in Ghasemababdi dance in relation to rice farming rituals, which is raised in light of the crucial role that women play in this dance and the implementation of rice farming customs. The current research is theoretical in nature and methodology, with a descriptive and analytic approach serving its purpose. The method of data collection is library and field using the method of ethnography in the region, observation, interviews, registration, and the recording of information. Research indicates that women perform Ghasemababdi dance while demonstrating gratitude for the blessings of rice cultivation and adherence to its principles through the use of a variety of manual skills. In other words, the Ghasemababdi dance serves as a reflection of cultural diversity and human thought. It is through this form of movement that women joyfully demonstrate the concept of cereal making patterns; thus, they have acquired a legendary status. Therefore, as a mother goddess equivalent to Anahita, the mother of man and the mother of the earth, they are considered and worshiped. In other words, the continuation and extension of life and the aliveness of the role of women is embodied in the unconscious of a person in order to transmit blessing, bonding and healing